Weyl Semiconductor Te/Sb2Se3 Heterostructure for Broadband Photodetection and Its Binary Photoresponse by C60 as Charge‐Regulation Medium. Issue 21 (25th August 2021) - Zhang, Xingchao; Yang, Yunkun; Li, Zihan; Liu, Xianchao; Zhang, Chaoyi; Peng, Silu; Han, Jiayue; Zhou, Hongxi; Gou, Jun; Xiu, Faxian; Wang, Jun
Abstract: Recently, elemental semiconductor Tellurium (Te) has been proven as a novel Weyl semiconductor with nontrivial Weyl fermion nature, indicating wonderful application prospect in future topological optoelectronic devices. Herein, large‐area photodetectors (PDs) of Te/Sb2 Se3 and Te/C60 /Sb2 Se3 heterostructure are fabricated based on a molecular beam epitaxy (MBE)‐grown Te film, which is theoretically equivalent to parallel‐connection circuit due to special device architecture. The constructed Te/Sb2 Se3 PD exhibits high‐sensitivity and broad spectral detection region from visible (405 nm) to mid‐infrared (4500 nm) wavelengths benefited from efficient synergistic multi‐mechanism including photoconductive and photo‐thermoelectric effects, achieving outstanding performance parameters such as high peak of responsivity ( Ri ) of 110.8 A W −1, detectivity ( D* ) of 2.09 × 10 13 Jones, and fast rise time about 31 ms at 808 nm, respectively. Furthermore, by depositing C60 between Te and Sb2 Se3 as charge‐regulation medium, the novel binary photocurrent signal output phenomenon depending on wavelengths and optical power densities is observed in Te/C60 /Sb2 Se3 ternary system, for which related mechanism is also investigated combined with spectral absorption characteristics, energy‐band arrangement, and light regulation experiment. This work provides a new pathway to fabricate superior multifunctional Te‐based PD, indicating promising prospects applied to next‐generation broadband optoelectronic devices with light‐controlled logic signal recognition function. Abstract : Te‐film‐based heterostructure photodetectors (PDs) are in‐depth investigated. The constructed Te/Sb2 Se3 PD exhibits high‐sensitivity and broad spectral detection region from visible to mid‐infrared wavelengths with outstanding performance. Furthermore, by depositing C60 as charge‐regulation medium, the novel binary photocurrent signal output phenomenon (positive/negative response) depending on wavelengths and optical power densities is observed in the Te/C60 /Sb2 Se3 ternary system.